KOMUNIKASI POLITIK DALAM UPAYA DIVERSIFIKASI ENERGI DI PROVINSI KEPULAUAN BANGKA BELITUNG (STUDI KASUS PT THORCON) - Hairul Sandi Mantowi; Bahjatul Murtasidin; Novendra Hidayat (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This study discusses political communication in energy diversification efforts in the Bangka Belitung Archipelago Province, a case study by PT ThorCon. This study uses a qualitative method with a descriptive design. The subjects of this study were residents of Batu Beriga Village, Batu Beriga Village Government, PT ThorCon, Bangka Belitung Provincial Government represented by DISKOMIFO, Bangka Belitung Provincial Energy and Mineral Resources Office, and Bangka Belitung Provincial PUPR Office who were selected through a purposive sampling technique. Data collection was carried out through observation and unstructured interviews. The results of the study show that PT ThorCon adopts a political communication approach that emphasizes credibility, attractiveness, equality, and power. First, PT ThorCon builds credibility by demonstrating expertise and knowledge in the energy sector. They collaborate with the government, related actors, and energy experts to obtain support regarding PLTT. Second, PT ThorCon uses a propaganda strategy to attract public interest. They visualize the benefits of PLTT directly and explain its contribution to the environment and the local economy. In this way, they are trying to convince the public that PLTT construction will have a positive impact on society. Lastly, PT ThorCon also utilizes power as a political communication strategy. They forge close ties with the government and related power actors. In this case, they take advantage of their political relations and power in influencing political decisions related to energy and investment policies.